The Quality of Human Resources in Improving Community in Bandar Lampung City - Ida Farida; Muhammad Ardiansyah; Masayu Nila Juwita (Publik : (Jurnal Ilmu Administrasi), 2022)
This research reveals how the quality of human resources exists in the public service office in the City of Bandar Lampung. The element of the problem found in the depths by seeing how the change of the service pattern that exists in society is mainly in the use of digital services (E-government) for that Capacity of Officers, Employee Placement, Authority, Responsibility as well as Motivation of Officials in performing service based on the main tasks and functions of the District Officer in the City of Bandar Lampung need to be reviewed to get a good quality of human resources. The type of research used is the Qualitative Method using a case study approach. The results of the study found that there is an influence of the capacity of employees on the technological tendency to support the digital government services (Electronic Government) in the area so that good governance is realized, the placement of employees in accordance with their expertise, the authority of responsibility of each employee as well as the motivation is still a factor in achieving the quality of human resources in providing services in the district of the city of Bandar Lampung.